Asymptotic stability of delayed fractional-order fuzzy neural networks with impulse effects. Issue 15 (October 2018) - Chen, Jiyang; Li, Chuandong; Yang, Xujun
Abstract: In this paper, we investigate the asymptotic stability of fractional-order fuzzy neural networks with fixed-time impulse and time delay. According to the fractional Barbalat's lemma, Riemann–Liouville operator and Lyapunov stability theorem, some sufficient conditions are obtained to ensure the asymptotic stability of the fractional-order fuzzy neural networks. Two numerical examples are also given to illustrate the feasibility and effectiveness of the obtained results.